2019
DOI: 10.1186/s13054-019-2394-9
|View full text |Cite
|
Sign up to set email alerts
|

Sedation practices and clinical outcomes in mechanically ventilated patients in a prospective multicenter cohort

Abstract: Objectives We sought to study the association between sedation status, medications (benzodiazepines, opioids, and antipsychotics), and clinical outcomes in a resource-limited setting. Design A longitudinal study of critically ill participants on mechanical ventilation. Setting Five intensive care units (ICUs) in four public hospitals in Lima, Peru. Patients One thousand six hundred fifty-seven critically ill partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 35 publications
6
50
1
5
Order By: Relevance
“…The administration of sedative drugs is a nearly universal intervention in mechanically ventilated intensive care unit (ICU) patients ( Patel and Kress, 2012 ). Appropriate sedation management is one effective method of improving patient tolerance of mechanical ventilation and reducing psychological stress in critically ill patients in the ICU ( Weinert and Calvin, 2007 ; Patel and Kress, 2012 ); however, the use of an inappropriate sedation strategy may increase the risk of all-cause mortality, delay ventilator weaning, and prolong the duration of hospitalization in ICU patients undergoing mechanical ventilation ( Shehabi et al, 2012 ; Shehabi et al, 2013b ; Shah et al, 2017 ; Shehabi et al, 2018 ; Aragón et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The administration of sedative drugs is a nearly universal intervention in mechanically ventilated intensive care unit (ICU) patients ( Patel and Kress, 2012 ). Appropriate sedation management is one effective method of improving patient tolerance of mechanical ventilation and reducing psychological stress in critically ill patients in the ICU ( Weinert and Calvin, 2007 ; Patel and Kress, 2012 ); however, the use of an inappropriate sedation strategy may increase the risk of all-cause mortality, delay ventilator weaning, and prolong the duration of hospitalization in ICU patients undergoing mechanical ventilation ( Shehabi et al, 2012 ; Shehabi et al, 2013b ; Shah et al, 2017 ; Shehabi et al, 2018 ; Aragón et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas one study found that light sedation with propofol did not affect the rate of asynchronies but deep sedation with propofol increased it [10], another found that deep sedation reduced but did not eliminate asynchronies [18]. A recent study showed that deep sedation, benzodiazepines, and cumulative doses of benzodiazepines were associated with higher mortality [19]. In another trial, patients on dexmedetomidine had slightly fewer asynchronies than those on propofol [20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a Peruvian multi-centre observational cohort study examining the relationship between benzodiazepine dose and mortality was published (45). In this study benzodiazepine dose was associated with a higher risk of mortality and a significant decrease in Vfd, although it should be noted that 98% of participants were deeply sedated at some point during the study and depth of sedation was assessed using either the Glasgow Coma Scale, Ramsay Sedation Scale or RASS.…”
Section: Discussionmentioning
confidence: 98%